Consumer complaining behavior : consumers' evaluations on service recovery strategies - Ahmad, Norzie Iriani (2001)
Much of the service recovery research to date has attempted to identify and classify service encounters from either the customer's or employee's perspective. This research tends to examine the relative importance of service recovery activities in determining overall satisfaction and consequent behavioral intentions, thus, trying to identify and classify service delivery failures and recovery strategies i particular Pizza Hut and Shakeys' Pizza restaurants. In this research, a non-probability sampling in which units of the sample are selected based on the convenience of the researcher was used for the sample purposes. As its name implies, convenience sampling involved collecting information from members of the population who were conveniently available to provide it. A total of 350 sets of questionnaires were distributed to Pizza Hut and Shakey's patrons. Of 323 returned questionnaires, 23 had incomplete information and were deemed invalid for this research. The data were analyzed using descriptive and inferential analysis. Furthermore, alpha coefficients were computed for scale reliability. Finding indicates that basically, for any given service failure, offering the customer coupons or managerial intervention, increased positive future intentions toward the provider, but interestingly, in this study, it was found that even the effective recovery effort has taken in place, yet it's still led the customers to switch. The most important findings is that if the number of switching customers as well as their intention to spread negative word-of-mouth to be reduced, enhancing coupon, discount and managerial intervention as part of the recovery strategies are necessary. Customers' future intentions toward the provider depended on the type of service failures and service recovery strategies to compensate the incident. From the service provider's perspective, considering core service failures, getting it right the first time is the best strategy for a service firm.